Preparation and toughening mechanism of Al2O3 composite ceramic toughened by B4C@TiB2 core–shell units - Shi, Yingjie; Li, Weixing; Zhang, Xiaorong; Jin, Jiachao; Wang, Jilin; Dong, Yu; Mu, Jingbo; Wang, Guangsuo; Zhang, Xiaoliang; Zhang, Zhixiao (Tsinghua University Press Ltd, 2023)
In this paper, the concept of incorporating core–shell structured units as secondary phases to toughen Al2O3 ceramics is proposed. Al2O3 composite ceramics toughened by B4C@TiB2 core–shell units are successfully synthesized using a combination of molten salt methodology and spark plasma sintering. The synthesis of B4C@TiB2 core–shell toughening units stems from the prior production of core–shell structural B4C@TiB2 powders, and this core–shell structure is effectively preserved within the Al2O3 matrix after sintering. The B4C@TiB2 core–shell toughening unit consists of a micron-sized B4C core enclosed by a shell approximately 500 nm in thickness, composed of numerous nanosized TiB2 grains. The regions surrounding these core–shell units exhibit distinct geometric structures and encompass multidimensional variations in phase composition, grain dimensions, and thermal expansion coefficients. Consequently, intricate stress distributions emerge, fostering the propagation of cracks in multiple dimensions. This behavior consumes a considerable amount of crack propagation energy, thereby enhancing the fracture toughness of the Al2O3 matrix. The resulting Al2O3 composite ceramics display relative density of 99.7%±0.2%, Vickers hardness of 21.5±0.8 GPa, and fracture toughness 6.92±0.22 MPa·m1/2.